2017
DOI: 10.18632/oncotarget.15190
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing RNA sequencing for global, unbiased evaluation of two new adjuvants for dendritic-cell immunotherapy

Abstract: Effective stimulation of immune cells is crucial for the success of cancer immunotherapies. Current approaches to evaluate the efficiency of stimuli are mainly defined by known flow cytometry-based cell activation or cell maturation markers. This method however does not give a complete overview of the achieved activation state and may leave important side effects unnoticed. Here, we used an unbiased RNA sequencing (RNA-seq)-based approach to compare the capacity of four clinical-grade dendritic cell (DC) activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Our data demonstrated that pRNA upregulated cytokines and migration-related genes in CD1c + mDCs as well as type I and III interferons (IFN-α and IFN-λ) related genes in pDC. Moreover, we demonstrated that pRNA stimulation increased expression of maturation markers (i.e., CD80, PD-L1 & CD40) in both CD1c + mDC and pDC, in addition to increase in immunostimulatory cytokines i.e., TNFα and INFα for CD1c + mDC and pDC, respectively ( 27 ). To investigate whether changes in metabolism are required for human DC-subsets immune response, we analyzed expression of OXPHOS related genes in human CD1c + mDC and pDC.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our data demonstrated that pRNA upregulated cytokines and migration-related genes in CD1c + mDCs as well as type I and III interferons (IFN-α and IFN-λ) related genes in pDC. Moreover, we demonstrated that pRNA stimulation increased expression of maturation markers (i.e., CD80, PD-L1 & CD40) in both CD1c + mDC and pDC, in addition to increase in immunostimulatory cytokines i.e., TNFα and INFα for CD1c + mDC and pDC, respectively ( 27 ). To investigate whether changes in metabolism are required for human DC-subsets immune response, we analyzed expression of OXPHOS related genes in human CD1c + mDC and pDC.…”
Section: Resultsmentioning
confidence: 97%
“…pRNA has been shown to activate CD1c + mDCs and pDCs and induces them to release IL-12 and IFN-α, respectively ( 28 ). Previously, we analyzed the whole-transcriptome of human CD1c + mDC and pDC upon TLR7/8 stimulation ( 27 ). Our data demonstrated that pRNA upregulated cytokines and migration-related genes in CD1c + mDCs as well as type I and III interferons (IFN-α and IFN-λ) related genes in pDC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to effects modulated by vaccine regimen, platform, and immunisation route, there is ample evidence to suggest that gene expression following immunisation can be affected by adjuvant selection. Transcriptomic evaluation of nonhuman primates (NHP) and human responses to vaccine adjuvants, with and without vaccination, has largely been restricted to bulk and/or microarray analyses [66][67][68][69]. Using an NHP model to compare responses against the HIV Env antigen with eight different adjuvants, Francica et al [70] demonstrated using microarrays with whole blood RNA that TLR4 or 7 agonists had differential effects on the upregulation of inflammatory and IFN genes.…”
Section: Comparing Vaccine Regimens Andmentioning
confidence: 99%
“…Additionally, we investigate how these cultures affect both innate and adaptive immune cells. As stimulus, we use protamine–RNA complexes (pR), a previously described TLR7/8 agonist that induces high levels of both IL-12p70 and IFN-α in mDCs and pDCs, respectively [ 25 28 ]. This will prevent possible artifact effects previously detected upon combination of different TLR ligands [ 29 ] and better resemble the clinical studies on mDCs and pDCs that are being performed with this stimulus (NCT02574377, NCT02993315, and NCT02692976).…”
Section: Introductionmentioning
confidence: 99%